Collective dismissal: considerations on how it is being configured after the first court resolutions (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
There is a new legal configuration in the collective redundancies after the Labour Reform of 2012. For the first time in our country, this especial way of extinguishing labour contracts, based on economic, technical, organisational and production reasons, depends on the employer resolution and it is no longer required thatthe labour authority aproves it. This research paper covers the most relevant innovations in the new procedure: from the legal definition of the causes to implementit, and how the new law intends to make them more flexible, to the subjects involved in the procedure and their duties in orden to reach an agreement that ispart of the collective bargaining system. The role of the labour law courts is reallyrelevant in the definition of the new legal model and the first decisitions are verysignificant from this point of view. Here are our considerations of how collective dismissalis being configured according to this first court decisitions.
Keywords: Collective redundancies; Workforce reduction; Collective bargaining agreement to reduce workforce; External flexibility; Consultation period; “Good faith” obligations in collective redundancy process; Reasons for the collective redundancy; Labour authorit